Curar, fiscalizar e sanear: as ações médico-sanitárias no espaço público da cidade do Natal (1850-1889) - Araújo, Avohanne Isabelle Costa de (2015)
This research focuses on the effort to understand how medical and sanitizing knowledge along with taken measures were capable of carry out transformations in the public space the city of Natal in the period ranging from 1850 to 1889, as far as public health is concerned. In order to address this issue, three aspects will be taken into consideration: the medical and pharmacist practice, the inspection of foodstuff and urban planning of the city of Natal. In this sense, we use the following sources: Reports of Presidents of the Province of Rio Grande do Norte, active mail between the Presidents of the Province of Rio Grande do Norte and the Council of the city of Natal; minutes of the meetings held by Natal’s Council; stance codes; the documents of Public Health Inspection, newspapers (Correio Natalense, Liberdade and O Conservador) and the Imperial Laws (Constitution of 1824 and the Decree of the Central Departament of Hygiene). As a methodology for the treatment and analysis of the sources, we used paleographic reading and transcription, classification of the facts found in the documentation, crossing information obtained in the documentation with the historicity and conditions of production of the newspaper sources, table production and comparative studies related to other provincial scenarios in the Empire.